(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Koju NP, Chalise MK, Kyes RC. 2021. Pikas and People: Human-Pika (Ochotona) interaction in the Himalaya of Nepal. Biodiversitas 22: 5085-5091. This study examined human-pika (Ochotona) interaction in two protected areas of Nepal: Lamtang National Park (LNP) and Api Nampa Conservation Area (ACNA). We conducted the study between 2012 and 2017 and employed a combination of three qualitative sampling methods: observation of behavior (both humans and pikas), practices, and rituals of the local residents, pilgrims, tourists, and Yarsagumba (Ophiocordyceps sinesis) collectors; collection of folk stories; and focus group discussions with local residents to investigate the nature of human-pika interaction. Based on the collective data, three general themes relating to human-pika interaction emerged: 1) the perception of pikas as a respected entity; 2) effects of anthropogenic pollution on pikas, and 3) pikas as a traditional medicine. In LNP, the pika was respected as symbol of the Buddhist monk ‘Lama’. In contrast, at ANCA, the dried meat of pika was used by local people for traditional medicine. At both locations, there is an increasing human presence resulting in increased anthropogenic pollution. This, in turn, may present a potential risk to the pikas over the long term. Further investigation is needed to address the effects of anthropogenic activities on the pika and to ensure the health and viability of the pika population.